2022
DOI: 10.1001/jamaoto.2022.2131
|View full text |Cite
|
Sign up to set email alerts
|

Use of Intraoperative Frozen Section to Assess Final Tumor Margin Status in Patients Undergoing Surgery for Oral Cavity Squamous Cell Carcinoma

Abstract: ImportanceMethods of assessing final margin status in patients undergoing surgery for oral cavity squamous cell carcinoma, such as intraoperative frozen section histopathology (IFSH) taken from the tumor bed, may have limitations in accuracy.ObjectiveTo evaluate the accuracy and implications of using IFSH samples to assess tumor bed margins in patients undergoing surgery for oral cavity squamous cell carcinoma (SCC).Design, Setting, and ParticipantsThis cross-sectional study included 1257 patients who underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Frozen section analysis is a routinely used technique in daily clinical practice. However, this technique is prone to false negatives because only a tiny fraction of the specimen is evaluated 17,34 . In addition, the evidence to support this commonly used technique is lacking 35 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Frozen section analysis is a routinely used technique in daily clinical practice. However, this technique is prone to false negatives because only a tiny fraction of the specimen is evaluated 17,34 . In addition, the evidence to support this commonly used technique is lacking 35 …”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, this method has low sensitivity in predicting close or positive margins due to sampling and interpretation errors. [15][16][17] An intraoperative imaging modality is needed to assess margin status and adjust the resection plane if necessary to obtain a higher percentage of clear margins (≥5 mm). A study by de Koning et al showed a significant improvement of adequate resection margins in tongue cancer when using intraoperative ultrasound (US).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…JAMA Otolaryngology–Head and Neck Surgery has published several studies that were presented at the 2022 AHNS meeting. These include a study examining the relationship between tumor bed–sourced frozen sections and final pathological margins, which showed poor correlation between the two. Another study examined the results of checkpoint inhibition outside of clinical trials .…”
mentioning
confidence: 99%